Solar flare effect on low latitude asymmetric indices - Singh, Anand K.; Sinha, A.K.; Pathan, B.M.; Rawat, Rahul (My University, 2012)
Low latitude asymmetric (ASY) indices in addition to auroral electrojet (AE) indices have been widely used to monitor magnetic substorm phenomenon. However, low latitude ASY indices are strongly affected by various current systems in the magnetosphere and the ionosphere which may not have any direct relation with substorm activity. In this paper we investigate the effect of solar flares on non-substorm and substorm times ASY indices using solar flare and indices data during the solar cycles 22 and 23 (year 1986–2008). We observe that during quiet magnetospheric conditions, long-lasting intense solar flares generate asymmetry similar to substorm events in ASY indices. In addition, substorm time ASY indices are also substantially affected by intense solar flares.
Keywords: Solar flare; Substorm; Asymmetry